IMPLEMENTATION SERVICE ADMINISTRATION POPULATION THROUGH WEBSITE “PLAVON DUKCAPIL" IN KALANGANYAR VILLAGE, SEDATI DISTRICT, SIDOARJO REGENCY - Magfiroh, Lailatul; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: Objective: This study aims to evaluate the implementation of population administration services through the Plavon Dukcapil website in Kalanganyar Village, Sedati District, Sidoarjo Regency as an innovation in digital-based public services. Method: The research employed a descriptive qualitative method with purposive sampling, involving village officials and community members as informants. Data were collected through interviews, observations, and documentation, and analyzed using the Miles & Huberman interactive model. Based on George C. Edward III's policy implementation theory, the study highlights that communication, resources, disposition, and bureaucratic structure are key dimensions influencing the effectiveness of this digital service. Results: The findings reveal that Plavon Dukcapil has improved service accessibility, reduced queues at the village office, and enhanced time and cost efficiency. However, the implementation is not yet optimal due to several challenges, such as low digital literacy among residents, limited capacity of village officials, technical system disruptions, and insufficient socialization efforts. Novelty: The novelty of this research lies in its focus on the implementation of Plavon Dukcapil at the village level, emphasizing both inhibiting factors and improvement strategies to ensure that digital public service innovation can achieve greater effectiveness and inclusion.